Nigeria : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper on Nigeria highlights challenges faced by the country in building on the achievements of 2004. The authorities will have to maintain macroeconomic stability while implementing ambitious structural reforms aimed at reducing the costs of doing business in Nigeria and supporting faster growth and poverty reduction. The government's ambitious and broad-based medium-term economic reform strategy and the National Economic Empowerment and Development Strategy aim to break with the misguided government-led development paradigm of the past that created a difficult environment for the private sector.